Evaluation of Prager and Chaboche models for reliable prediction of elastoplastic behaviour in low-cycle fatigue - Aboussalih, Amira; Hammoudi, Salah; Fedaoui, Kamel; Arar, Karim; Baroura, Lazhar (Technology audit and production reserves, 2025)
The object of this research is the cyclic elastoplastic behavior of materials, principally austenitic stainless steel (304L). The paper studies the 304L stainless steel behavior of exposed to different uniaxial and multiaxial cyclic loadings. It also determines the accuracy with which classical models, such as the Prager model, reproduce the phenomena of work hardening. All the models have which limits the reliability of fatigue life predictions for structures. For that, in this numerical study, a comparative analysis is performed between the Prager model and the Chaboche model. Chaboche model was selected to overcome the shortcomings of classical approaches, it can incorporate isotropic and nonlinear kinematic work hardening together. Numerous numerical simulations were conducted under various loading scenarios allowed to estimate the predictive capacity of the constitutive models and the limitations of simplified linear approaches. The results obtained, show that Chaboche model reproduces with excellent accuracy the phenomena of work hardening, additional work hardening, and ratcheting compared to the Prager model. This is explained by the fact that the Chaboche model can take into account the coupling between different phenomena which guarantees a realistic representation of cyclic elastoplastic behavior. Compared to similar models known in the literature, the Chaboche approach offers significant advantages: increased predictive accuracy, better representation of complex cyclic phenomena, and a fatigue life assessment of 304L stainless steel that closely reflects reality in demanding industrial applications.